Inovasi Pemenuhan Nutrisi Ternak: Penyuluhan Perawatan Anak Domba dan Pembuatan Mineral Blok di Desa Pekasiran - Putri, Azzahra Cahyarani; Mukti Ichsan Fariz; Oktaviani, Widya; Fitriani, Alifia Tul; Ritonga, Khairil Abdy; Tulus, Ananda Putri; Theresia, Claudina; Wijaya, Bara Muhammad Adi; Wijayanti, Indah (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2024)
The development of the livestock sector in Indonesia, particularly for sheep farming, still faces many challenges. Farmers continue to use traditional methods, resulting in slow growth of livestock and suboptimal profits. Mineral blocks are supplemental feed designed to enhance the adequacy of energy, protein, and minerals, as well as to improve the palatability of ruminant animals in block or cylindrical forms. Milk replacer is a substitute milk for livestock, expected to help provide nutrients for pre-weaned lambs. The outreach program on lamb care and mineral block production aims to increase the knowledge, awareness, and interest of farmers in Pekasiran Village regarding the nutritional needs of livestock through the provision of milk replacer and mineral blocks. The methods used in the implementation of the program include direct observation of farms, interviews, mapping, distributing invitations to farmers in Pekasiran Village, conducting trials of mineral blocks, outreach by providing materials on lamb care and mineral block production, demonstrations, and interviews with farmers present at the outreach event. This activity was attended by 38 breeders with a total of around 720 livestock. The outreach activities were carried out in collaboration between KKN-T students from IPB University and CV. Al Mumayyaz Group. During the program, it was found that the farmers were very enthusiastic about participating, actively discussing with the resource persons, and they were able to demonstrate the production of mineral blocks correctly and effectively. This activity also contributed to improving the health and productivity of livestock, as well as the well-being of farmers in Pekasiran Village. Farmers are expected to be able to implement better and more innovative practices in livestock management so that they can contribute to increasing efforts to develop livestock potential in Pekasiran Village.